A Study on Role of Ultrasonography in the Diagnosis of Dengue Fever - Naidu, Y. Thathayya; R. Kiranmai (Asian Journal of Medical Radiological Research, 2020)
Background: Dengue Fever is an acute mosquito transmitted viral infection caused by one of the 4 serotypes of the genus flavivirus which has become a major international public health problem. The diagnosis of DF is often delayed owing to time taken for availability of serology test results. Moreover, this test is expensive and not widely available. Ultrasonography (USG) is a cheap, rapid and widely available non-invasive imaging method. In recent years several studies concluded that Ultrasonography of the chest and abdomen can be an important adjunct to clinical profile in diagnosis of DF and diagnosis can be made early in the course of the disease compared with other modes of diagnosis. The aim of the study is to demonstrate the ultrasound findings of dengue fever and also evaluate the specificity of gall bladder findings in dengue fever. Subjects and Methods: We conducted a prospective study in Govt Medical College& Hospital, Srikakulam and Konaseema Institute of Medical Sciences, Amalapuram, A.P. Study included 50 patients referred to the department of Radio-Diagnosis and Imaging for Ultrasonography with clinical suspicion of dengue fever, during a period of July 2018 to December 2019. USG of the abdomen, pelvis and chest was performed in all cases and findings were noted. Dengue serology was performed later and all the ultrasound findings were correlated with dengue serology. Results: In our study of 50 patients all the patients studied were diagnosed with dengue fever based on dengue serology. In our study, 100% of our patients diagnosed with DF (by dengue serology) showed gall bladder wall thickening, 88% showed splenomegaly, 44% showed ascites. Pleural effusion was present in 30% of which 66.66% of pleural effusion was bilateral and the rest 33.33% was right sided. Isolated left sided pleural effusion was not found in our study. Hepatomegaly was present in 28% of our patients. In our study mortality and complications from dengue fever were not seen. Conclusion: Ultrasound findings in dengue fever are gall bladder wall thickening, splenomegaly, ascites, pleural effusion and hepatomegaly. In an area where DF is an epidemic, when Ultrasonography shows gall bladder wall thickening in a febrile patient with thrombocytopenia DF should be suggested On Ultrasonography, when there is gall bladder wall thickening, splenomegaly, ascites, and pleural effusion in a febrile patient with thrombocytopenia in a DF epidemic area a diagnosis of DF should be considered in a differential diagnosis until proved otherwise.